OCCURRENCE OF MATURE SPECIMENS OF METAPENAEUS BURKENROADI KUBO IN THE PULICAT LAKE - Muthu, M S; Manickam, P E Sampson (Indian Journal of Fisheries, 2011)
Mature females and males of Metapenaeus burkenroadi with fully developedovaries and petasmae were collected from the Pulicat lake in January1972. The possibility of their breeding inside the lake and the feasibility ofutilizing this species for culturing in the Pulicati lake are indicated. Somemorphological features of the specimens which are at variance with previousdescriptions of the species are pointed out